Effect of organic manures on plant growth and root yield of safed musli (Chlorophytam borivilianum) under agro-climatic condition of eastern Uttar Pradesh - Ram, D.; Thenua, O.V.S.; Chandra, R. (Annals of Agricultural Research, 2016)
A field experiment was conducted during 2008-09 at Faizabad, Uttar Pradesh to study the effect of organic manures on plant growth and root yield of safed musali (Chlorophytum borivilianum Sant. & Fer.). The experiment was laid-out in randomized block design with 10 treatments and replicated thrice. An application of Farmyard manure (FYM) at 20 tonnes/ha resulted in the maximum number of leaves (14.1), length of leaf (27.97 cm), width of leaf (1.63 cm), length of spike (36.92 cm), number of fasciculated roots/plant (12.73), length of roots (8.19 cm), diameter of roots (5.87 mm), fresh root yield (48.42 q/ha) and dry root yield (8.45 q/ha) compared to all other treatments.